Hepatocyte Growth Factor Ameliorates Hyperglycemia and Corrects β-Cell Mass in IRS2-Deficient Mice - Alvarez-Perez, Juan C. (Mol Endocrinol, 2014)
Insulin resistance, when combined with decreased β-cell mass and relative insufficient insulin secretion, leads to type 2 diabetes. Mice lacking the IRS2 gene (IRS2(−/−) mice) develop diabetes due to uncompensated insulin resistance and β-cell failure. Hepatocyte growth factor (HGF) activates the phosphatidylinositol 3-kinase/Akt signaling pathway in β-cells without recruitment of IRS1 or IRS2 and increases β-cell proliferation, survival, mass, and function when overexpressed in β-cells of transgenic (TG) mice. We therefore hypothesized that HGF may protect against β-cell failure in IRS2 deficiency. For that purpose, we cross-bred TG mice overexpressing HGF in β-cells with IRS2 knockout (KO) mice. Glucose homeostasis analysis revealed significantly reduced hyperglycemia, compensatory hyperinsulinemia, and improved glucose tolerance in TG/KO mice compared with those in KO mice in the context of similar insulin resistance. HGF overexpression also increased glucose-stimulated insulin secretion in IRS2(−/−) islets. To determine whether this glucose homeostasis improvement correlated with alterations in β-cells, we measured β-cell mass, proliferation, and death in these mice. β-Cell proliferation was increased and death was decreased in TG/KO mice compared with those in KO mice. As a result, β-cell mass was significantly increased in TG/KO mice compared with that in KO mice, reaching levels similar to those in wild-type mice. Analysis of the intracellular targets involved in β-cell failure in IRS2 deficiency showed Pdx-1 up-regulation, Akt/FoxO1 phosphorylation, and p27 down-regulation in TG/KO mouse islets. Taken together, these results indicate that HGF can compensate for IRS2 deficiency and subsequent insulin resistance by normalizing β-cell mass and increasing circulating insulin. HGF may be of value as a therapeutic agent against β-cell failure.